International students’ satisfaction with university foodservice and its influence on word-of-mouth communication in research universities in Malaysia - Akbara, Anisa Zahwa (2019)
Malaysia aims to host 250,000 overseas students by the year 2025 as international student admissions are important for establishing Malaysia as an advanced education center in the world. Apart from economic advantages, efforts are also made to attract foreign students to improve the universities’ reputation. It is therefore critical to evaluate the international students' perception of their university experience in Malaysia including their experience with on-campus dining. As foodservice is a fundamental factor influencing student satisfaction, students would be disappointed if the on-campus foodservice dining facilities do not meet their needs and wants. A satisfied student population is a source of favorable outcomes, such as in spreading positive word of mouth (WOM) and recommending the university to others. Consequently, this study attempted to measure the effect of university foodservice attributes satisfaction on word of mouth behavior among international university students. In addition, this study also aimed to examine student satisfaction with on-campus foodservice using the importanceperformance analysis (IPA) technique. A quantitative research approach using survey research design was employed in this study. A total of 620 international students who were studying in Malaysian research universities (MRU) in Malaysia were selected as the sample of this study. A structured questionnaire was designed. Using the structural equation modeling (SEM) technique, this study revealed that interactional quality, atmospheric quality, price fairness, and food selection significantly explained customer satisfaction by 50.4%. Moreover, 43.7% of variance in word of mouth behavior was significantly explained by food quality and customer satisfaction. Customer satisfaction was found to mediate the relationship between all foodservice attributes (except food quality) and word of mouth behavior. The results of IPA matrix showed that food price was the key driver of customer satisfaction and the management’s job was to ensure that the university foodservice ‘‘keeps up the good work”. Nonetheless, food quality was considered to be underperforming and as such, represented the product's major weakness. This study has examined the factors that can boost the market share for colleges and education service providers, with enduring impacts on the campus and its students. Theoretically, the findings shed light on international students’ satisfaction with Malaysian public universities’ foodservice. From a practical perspective, the findings provide a framework in developing an effective marketing strategy for universities. If on-campus foodservice fulfills students’ needs and wants, it could trigger positive word of mouth when they return to their home country and become advocates for the university.